2017
DOI: 10.1016/j.egja.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Rocuronium versus dexmedetomidine as an adjuvant to local anesthetics in peribulbar block: A double blind randomized placebo controlled study

Abstract: a b s t r a c tObjective: To compare the use of rocuronium with that of dexmedetomidine as an adjuvant to the local anesthetic mixture in peribulbar anesthesia for cataract surgery. Design: A double blind, prospective, randomized controlled study. Methods: Ninety patients with cataract in the age group 18-80 years of American Society of Anesthesiologists (ASA) physical status I-III scheduled for elective cataract surgery under regional anesthesia were randomly divided into three groups; Group C (control) recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…It may also facilitate drainage of aqueous humor by reducing the sympathetic mediated vasomotor tone of the drainage system of the eye. [ 17 18 ] Our results were similar to those obtained by Channabasappa et al . [ 19 ] who reported that a combination of bupivacaine and lidocaine with dexmedetomidine in peribulbar anesthesia helped to decrease the IOP significantly.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…It may also facilitate drainage of aqueous humor by reducing the sympathetic mediated vasomotor tone of the drainage system of the eye. [ 17 18 ] Our results were similar to those obtained by Channabasappa et al . [ 19 ] who reported that a combination of bupivacaine and lidocaine with dexmedetomidine in peribulbar anesthesia helped to decrease the IOP significantly.…”
Section: Discussionsupporting
confidence: 92%
“…Dexmedetomidine is a highly specific centrally acting α2-agonist; it is widely used nowadays with local anesthetic mixture in peripheral nerve blocks, subarachnoid anesthesia,[ 30 ] and ophthalmic anesthesia. [ 17 ] Alpha 2-agonists acts peripherally by reducing the discharge of norepinephrine and by inhibition of nerve fiber action potential while their central analgesic effect is produced at the level of the dorsal root neuron in pain pathway as well as at the locus coeruleus by preventing the release of substance P and by activation of α2-receptors, respectively. [ 18 ]…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the addition of 50 mg magnesium sulphate to local anesthesia in older (40-80 years-old) patients who underwent cataract surgery did not show any benefit regarding the onset of block or akinesia score [23]. AbdAlali et al [19] reported better analgesic and anesthetic effects of rocuronium as an additive to local anesthetic drugs in the peribulbar block than magnesium sulphate.…”
Section: Discussionmentioning
confidence: 99%
“…Using dexmedetomidine, and magnesium sulphate as adjuvants to peribulbar anesthesia has been investigated in several studies [18][19][20], comparing their effects versus rocuronium in peribulbar anesthesia [19,21] has been studied as well. To our knowledge little was done to investigate the local effects of dexmedetomidine or magnesium on the muscle relaxant potentiated block.…”
Section: Introductionmentioning
confidence: 99%